Self Help Groups are Powerful Entrepreneurial Hub at the Grassroots level of India - Sivasubramanian, M.; Saifil Ali, Dr. M.I. (Journal of Contemporary Research in Management (JCRM), 2013)
Sustained development in an economy aims at betterment of people through social equality, economic development and environmental conservation. This could be achieved by eradication of poverty, social equality, in terms of providing education, health awareness, human security and right to access the available resources. Therefore, economists are always looking for a new alternative system to reduce economic imbalance. Self Help Groups (SHG), a successful program in developing countries, has fulfilled it. This paper, part of research study undertaken by the authors on the flow of credit to groups and changes made in the bottom level micro entrepreneurs, who shapeup the entrepreneurial propensity among the co- members. Data were collected through structured interview schedules from SHG members having account with nationalized bank’s rural branches in two districts of Tamilnadu. Appropriate statistical tools were used to analyse the data. Based on the findings, suitable suggestions were made to create entrepreneurial hubs. This study helps the policy makers in the government, banking sector and other financial services to enhance the credit flow to SHGs so that it cultivate entrepreneurial culture in the society. Further, researches could be undertaken on influence of group cohesiveness on developing entrepreneurial activities and structural changes in the skills of group members.